Deferasirox – a rarer cause of Fanconi syndrome - Khan, Iman (J Community Hosp Intern Med Perspect, 2019)
Deferasirox is a recently approved iron chelator and is widely used to treat iron overload in transfusion-dependent patients. Its once-daily dosing and oral route of administration have made it an appealing alternative to deferoxamine. Recent case studies have brought to light its potential to cause damage to the proximal convoluted tubule resulting in Fanconi syndrome (FS). FS is a proximal tubular dysfunction that leads to glycosuria, phosphaturia, aminoaciduria, and normal anion gap metabolic acidosis. Herein, we discuss a case of a young male on chronic blood transfusions requiring deferasirox therapy, who was found to have FS from its use. We discuss the possible mechanism of drug toxicity and the need for regular monitoring of serum electrolytes andurinalysis along with renal function tests to avoid this consequence.